EXPERIMENTAL-DETERMINATION OF FE AND MG EXCHANGE BETWEEN GARNET AND OLIVINE AND ESTIMATION OF FE-MG MIXING PROPERTIES IN GARNET - Hackler, R; Wood, B (1989)
The partitioning of Fe and Mg between garnet and olivine has been determined as a function of Fe/Mg ratio at 1000°C and 9.1 kbar. Garnets of composition XgtFe = 0.90, 0.82, 0.60, 0.51, and 0.35 were mixed with olivines of various compositions in a ratio of 10:1 by mass, and the equilibrium olivine composition was determined within narrow limits. The magnitudes of the garnet interaction parameters are highly correlated with those of the olivine solution. However, assuming WolFeMg = WolMgFe = 9000 J/mol (two-site basis), we obtain WgtFeMg 2080 ± 1250 J/mol and WgtMgFe = 6350 ± 880 J/mol (three-site basis) at 1000°C. The standard-state free-energy change of the exchange reaction is calculated to be -2000 ± 800 J at 1000°C and 1 bar, in agreement with recent estimates of the free energy of almandine. -from Authors